The need for biochemical testing in beta‐enolase deficiency in the genomic era. Issue 1 (3rd September 2019) - Wigley, Ralph; Scalco, Renata S.; Gardiner, Alice R.; Godfrey, Richard; Booth, Suzanne; Kirk, Richard; Hilton‐Jones, David; Houlden, Henry; Heales, Simon; Quinlivan, Ros
Abstract: Glycogen storage disease type XIII (GSDXIII) is a very rare inherited metabolic myopathy characterized by autosomal‐recessive mutations in the ENO3 gene resulting in muscle β‐enolase deficiency, an enzymatic defect of the distal part of glycolysis. Enzyme kinetic studies of two patients presenting with exertion intolerance and recurrent rhabdomyolysis are reported. Next generation sequencing confirmed patient 1 was homozygous for p.E187K in ENO3, while patient 2 was homozygous for p.C357Y. ENO3 variants pathogenicity was confirmed by functional studies in skeletal muscle. p.E187K caused extremely low total enolase activity. p.C357Y was associated with a higher level of residual activity but kinetic studies showed a lower maximum work rate ( V max ). This study illustrates that GSDXIII may be caused by either null mutations leading to β‐enolase deficiency or by mutations that alter the enzyme's kinetic profile. This study highlights the importance of carrying out functional studies as part of the diagnostic process following the identification of variants with next generation sequencing.